(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Drug addiction is one of the major problems of India which affects thousands of people each year. Drug addiction is the existence of both physical dependence and psychological dependence on at least one illicit substance. It is a chronic disease of brain that compels the brain into a thought that drugs are essential regardless of its adverse results. People often use drugs as an outlet for their problems although drug use creates its own problems over time. Drugs are not only influence a person’s health and relationships, but also crash society and surroundings. It can be sought out by understanding its causes and consequences with a great passion. A treatment procedure must be followed in some critical conditions. There are a lot of treatment alternative to guide people towards healthy and stress free life.